The Study of Wave Run-up by Varying Roughness Pattern - Azahar, Ahmad Zahin (Universiti Teknologi PETRONAS, 2017)
Coastal area profiles have natural resources and environment, physical setting, fishing and agriculture, tourism and socio-economic activities. These activities usually conducted on the area called coastal zone. Coastal zones are dominated by a high percentage of the population in that area (Ragenbogen, 2014). This is because of it acts as main attraction of economic activities, such as oil and gas exploration, transportation, communication, urbanization and agriculture. Nowadays, as Malaysia with the status of developing country, most of the coastal zones has been damage by the impact due to all of these development activities from various sectors.